Ecdysone-Related Biomarkers of Toxicity in the Model Organism Chironomus riparius: Stage and Sex-Dependent Variations in Gene Expression Profiles. - Rosario Planelló; Óscar Herrero; Pablo Gómez-Sande; Irene Ozáez; Fernando Cobo; María J Servia (PLoS ONE, 2015)
Despite being considered a model organism in toxicity studies, particularly in assessing the environmental impact of endocrine disrupting compounds (EDCs) and other chemicals, the molecular basis of development is largely unknown in Chironomus riparius. We have characterized the expression patterns of important genes involved in the ecdysone pathway from embryos to pupa, but specially during the different phases of C. riparius fourth larval instar, according to the development of genital and thoracic imaginal discs. Real-Time PCR was used to analyze: EcR and usp, two genes encoding the two dimerizing partners of the functional ecdysone receptor; E74, an early response gene induced by ecdysteroids; vg (vitellogenin), an effector gene; hsp70 and hsc70, two heat-shock genes involved in the correct folding of the ecdysone receptor; and rpL13, as a part of the ribosomal machinery. Our results show for the first time stage and sex-dependent variations in ecdysone-responsive genes, specially during the late larval stage of C. riparius. The induction in the expression of EcR and usp during the VII-VIII phase of the fourth instar is concomitant with a coordinated response in the activity of the other genes analyzed, suggesting the moment where larvae prepare for pupation. This work is particularly relevant given that most of the analyzed genes have been proposed previously in this species as sensitive biomarkers for the toxicological evaluation of aquatic ecosystems. Identifying the natural regulation of these molecular endpoints throughout the Chironomus development will contribute to a more in-depth and accurate evaluation of the disrupting effects of EDCs in ecotoxicological studies.